Effect of water depths on the growth, yield, and proteome patiern of lowland rice in Silabukan soil - Liew, Xi Yun (2016)
Effects of deeper ponding water depth on plant growth have received renewed attention because of the subsurface irrigation and water table conditions in large sized rice fields. Moreover, rice plants are sensitive to water stress and it will influence the rice yield produced. A study was conducted to evaluate the effect of different water depths on the growth, yield, and proteome pattern of TR8 and TR9 rice varieties in Silabukan soil. The reasons to carry out this study were because there is variation in water depth due to irregularity of levelling, different cultural practices of farmers as they tend to keep different water depths in planting wetland rice, and the increasing of ponding water especially during rainy seasons. In this study, TR8 and TR9 rice varieties were planted in three water depths of 5, 10, and 15 cm with three replicates each under rain shelter covered by zinc plates and net. Rice roots of TR9 rice variety in 5 cm (control) and 15 cm water depths (stressed condition) were harvested at late booting stage for proteome analysis. Trichloroacetic (TCA) acetone method was used for protein extraction. Sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) was done to compare protein profiling in these two water depths with three biological replicates. Results indicated that there was no interaction between different water depths with different rice varieties on the growth and yield. However, TR9 rice variety was found to have better yield than TR8 rice variety under different water depths in Silabukan soil. The mean extrapolated yield of TR9 rice variety showed 0.9 tons/ha more than TR8 rice variety. In SDS-PAGE analysis, one band was found differently expressed in 15 cm water depth. This band could be related to the mechanism of rice crops during waterlogging stress.